2001
DOI: 10.1128/aac.45.5.1561-1564.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Itraconazole Oral Solution in Neutropenic Children during Long-Term Prophylaxis

Abstract: We investigated the pharmacokinetics and safety of an oral solution of itraconazole in two groups of neutropenic children stratified by age. Effective concentrations of itraconazole in plasma were reached quickly and maintained throughout treatment. The results indicate a trend toward higher concentrations of itraconazole in plasma in older children.Invasive fungal infections are frequently observed in neutropenic patients (4). Several antifungal agents are available to treat and prevent invasive mycoses, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 13 publications
1
26
0
2
Order By: Relevance
“…Adverse effects tend to be transient and may include gastrointestinal disturbances (Ͻ10%), hypertriglyceridemia (9%), hypokalemia and elevated levels of hepatic transaminases (5% each), and rash or pruritus, headaches or dizziness, and pedal edema (Ͻ2% each) (31). The favorable safety profile of oral CD-ITRA observed in pediatric patients enrolled in our study is consistent with that reported for immunocompromised pediatric patients with cancer or following liver transplantation and receiving the compound at 5 mg/kg QD (7) or 2.5 mg/kg BID (29) for approximately 14 days. These favorable safety data, however, stand somewhat in contrast to those of a third study that evaluated the safety and tolerance of CD-ITRA administered at dosages of 5 mg/kg QD and 2.5 mg/kg BID for a median duration of 37 days for antifungal prophylaxis in children undergoing hematopoietic stem cell transplantation (9).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Adverse effects tend to be transient and may include gastrointestinal disturbances (Ͻ10%), hypertriglyceridemia (9%), hypokalemia and elevated levels of hepatic transaminases (5% each), and rash or pruritus, headaches or dizziness, and pedal edema (Ͻ2% each) (31). The favorable safety profile of oral CD-ITRA observed in pediatric patients enrolled in our study is consistent with that reported for immunocompromised pediatric patients with cancer or following liver transplantation and receiving the compound at 5 mg/kg QD (7) or 2.5 mg/kg BID (29) for approximately 14 days. These favorable safety data, however, stand somewhat in contrast to those of a third study that evaluated the safety and tolerance of CD-ITRA administered at dosages of 5 mg/kg QD and 2.5 mg/kg BID for a median duration of 37 days for antifungal prophylaxis in children undergoing hematopoietic stem cell transplantation (9).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, both dosage regimens tested in this study yielded peak and trough drug levels similar to or slightly higher than those reported for immunocompromised adults receiving similar dosage regimens (2,24). In several studies, in comparison to the results for QD dosing, trough levels of ITRA and OH-ITRA were consistently higher after BID dosing with the same total daily dosage (7,24,29). Given the concentration-and time-dependent pharmacodynamics of the antifungal azoles (15), BID dosing thus appears more appropriate, despite the prolonged half-life that by itself would suggest QD dosing.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Results of studies examining the pediatric/juvenile pharmacokinetics of currently marketed azole antifungals, such as itraconazole (7,12,25), fluconazole (3,15,16,26), and voriconazole (29), have been published. Two studies (12,25) with itraconazole show similar peak and trough concentrations for pediatric and adult patients (17 patients, ages 2 to 18 years), and another (7) reports pediatric concentrations that were approximately one-third of those attained by adults (26 patients, ages 6 months to 12 years) (4,7,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although investigation of the pharmacokinetic profile of a drug in children is often delayed during the drug development process, results have been published of studies examining the pharmacokinetics in pediatric patients of currently marketed azole antifungals, such as itraconazole (7,12,25), fluconazole (3,15,16,26), and voriconazole (29). Pharmacokinetic profiles for itraconazole are inconsistent between pediatric patients and adults, and some pharmacokinetic parameters of fluconazole and voriconazole appear to differ between children and adults.…”
mentioning
confidence: 99%